Smaller radiator with enhanced heat transfer using CNT-nanofluids - Ismail, Ahmad Faris; Abd-Halim, B.A.; Walvekar , Rashmi Gangasa; Yusaf, Talal F. (WIT Press, 2014)
With the development of advanced thermal fluids such as carbon nanotubes (CNT)-nanofluids, which have better thermal conductivity, there is a possibility to reduce the size of car radiators without affecting their heat transfer performance. In this study, the heat transfer results are compared using the standard radiator and a smaller radiator using four different fluids acting as the coolants: water, ethylene glycol, 0.02% CNT-nanofluid and 0.1% CNT-nanofluid. The experimental results show that the stable CNT-nanofluids prepared in this work produce better heat transfer performance in both engines. Moreover, the smaller radiator using the CNT-nanofluids produces similar or better heat transfer rates compared to the standard radiator using water or ethylene glycol.